Application of Stokes' Theorem to electrically small loop antenna radiation. Issue 3 (July 2017) - Wu, Minghe; Teng, Baohua; Shen, Chutian; Balfour, Esmod Agurgo; Fu, Hao; Wu, Shaoyi; Li, Junjie
Stokes' Theorem is applied to derive the retarded vector potential of loop antennas for the radiation of electric field and magnetic field. Simulations of the ideal and the actual magnetic dipole antenna suggest a satisfactory agreement of the two antennas. The simulation results were further experimentally tested by the demonstration experiment, which indeed confirmed the simulation results. The direction of radiated electric field in the experimental setup is shown in a vivid way. The theoretical simplification and experimental design will significantly provide undergraduate students with an easier but better understanding of the radiation of an electrically small loop antenna.